A composite electrode material for lithium ion hybrid supercapacitor and preparation method thereof
By growing Co3O4 nanorods and attaching NiFe2O4 nanosheets on a three-dimensional reduced graphene oxide substrate, the problems of high energy density and high power density of lithium-ion hybrid supercapacitor electrode materials were solved, and superior electrochemical performance was achieved.
Patent Information
- Application Number
- CN202410950001.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-16
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-07-16
AI Technical Summary
Existing lithium-ion hybrid supercapacitor electrode materials struggle to simultaneously achieve high energy density, high power density, and excellent cycle life.
Co3O4@NiFe2O4/rGO composite material was used as the electrode material. Co3O4 nanorods were grown on a three-dimensional reduced graphene oxide substrate and NiFe2O4 nanosheets were attached to them. The synergistic effect of these materials was used to improve the electrode performance.
Achieving high energy density, high power density, and excellent cycle life, the Co3O4@NiFe2O4/rGO composite material exhibits higher specific capacitance and better electrochemical properties.
Smart Images

Figure CN118675903B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical energy storage devices, and in particular to a composite electrode material for a lithium ion hybrid supercapacitor and a preparation method thereof. Background Art
[0002] High power density supercapacitors (SC) and high energy density lithium-ion batteries (LIB) are matched and combined under appropriate conditions to achieve high power density and high energy density, and a hybrid energy storage device of supercapacitors and lithium-ion batteries, namely lithium-ion hybrid supercapacitors, has been developed. Lithium-ion hybrid supercapacitors have the advantages of relatively high power density, short charging time, long service life, long-term storage, and theoretically no maintenance. Lithium-ion hybrid supercapacitors are mainly composed of battery-type negative electrode materials, capacitor-type positive electrode materials, and electrolytes.
[0003] The electrode materials of supercapacitors include carbon materials, metal oxides, conductive polymer materials, etc. Carbon materials are generally used as the main materials, such as activated carbon, carbon nanotubes, carbon fibers, carbon aerogels, nanostructured mesoporous carbon, graphene, etc. Graphene is used as the electrode material of lithium-ion hybrid supercapacitors because it can increase the flexibility of the material and improve the ability to resist the volume effect during charging and discharging, thereby improving the cycle stability of the electrode material. Although graphene has significant performance in carbon materials, since graphene materials can only rely on the double electric layer for energy storage, the theoretical specific capacitance and energy density of supercapacitors are both low. Transition metal oxide pseudocapacitor materials, which can make up for this as electrode materials, have a larger energy density. However, when carbon materials and transition metal oxides are used as single electrode materials for lithium-ion capacitors, high energy density, high power density and excellent cycle life cannot be obtained at the same time. It is a new trend in the development of new electrode materials to compound carbon materials with transition metal oxides and use the synergistic effect between the two to prepare composite electrode materials with excellent performance. Therefore, it is urgent to develop a new type of composite electrode material to improve the energy density of hybrid capacitors. Summary of the invention
[0004] Purpose of the invention: In order to overcome the deficiencies in the prior art, the present invention provides a composite electrode material and a preparation method for a lithium-ion hybrid supercapacitor, and obtains a Co3O4@NiFe2O4 / rGO composite material, which achieves high energy density, high power density and excellent cycle life.
[0005] Technical solution: To achieve the above purpose, a composite electrode material for a lithium-ion hybrid supercapacitor includes nanorods composed of Co3O4; a plurality of NiFe2O4 nanosheet balls are attached to the surface of the nanorods composed of Co3O4.
[0006] Furthermore, the length of the nanorods composed of Co3O4 ranges from 1.9 μm to 2.4 μm, and the width of the nanorods ranges from 0.15 μm to 0.28 μm.
[0007] Furthermore, the diameter of the NiFe2O4 nanosheet spheres ranges from 2.3 μm to 2.8 μm.
[0008] Furthermore, a method for preparing a composite electrode material for a lithium-ion hybrid supercapacitor comprises the following steps:
[0009] S1-1, synthesizing graphene oxide GO solution by using improved Hummers method, soaking nickel foam in the graphene oxide GO solution for a certain period of time, and drying after soaking to obtain graphene oxide GO deposited on the nickel foam;
[0010] S1-2, placing the graphene oxide GO deposited on the nickel foam into a reactor lined with polytetrafluoroethylene, adding N2H4·H2O into the reactor, heating the reactor for reaction, taking out the reactor after the reaction is completed and cooling it to obtain a reduced graphene oxide rGO sample;
[0011] S1-3, soaking the reduced graphene oxide rGO sample in a mixed solution of FeCl3 and HCl for a certain period of time to etch and remove the nickel foam template;
[0012] S1-4, cleaning the reduced graphene oxide rGO sample from which the foam nickel template is etched away, and heating and drying the cleaned reduced graphene oxide rGO sample to obtain foam-type three-dimensional reduced graphene oxide rGO.
[0013] Furthermore, a method for preparing a composite electrode material for a lithium-ion hybrid supercapacitor further comprises the following steps:
[0014] S2-1, dissolve Co(NO3)2·6H2O and urea in H2O and stir until clear to obtain a mixed solution A;
[0015] S2-2, adding the mixed solution A into a reactor containing the treated foam-type three-dimensional reduced graphene oxide rGO substrate, and heating the reactor for reaction;
[0016] S2-3, using water to wash the reaction kettle after the reaction in step S2-2, and heating to dry;
[0017] S2-4, dissolve Ni(NO3)2·6H2O, Fe(NO3)3·9H2O, NH4F and urea in H2O, and stir until clear to obtain a mixed solution B;
[0018] S2-5, adding the mixed solution B into the reaction kettle dried in step S2-3, and heating for reaction;
[0019] S2-6, the precursor is washed with water after the reaction in step S2-5, and the reaction kettle is heated to dry, and the precursor is calcined at 345°C to 360°C for a certain time to obtain a Co3O4@NiFe2O4 / rGO composite material.
[0020] Furthermore, in step S1-2, the reactor is heated to react at a temperature of 80° C. to 95° C. for 5-7 hours.
[0021] Furthermore, in step S2-2, the reaction is carried out by heating the reactor to 110° C. to 130° C. and reacting for 4-8 hours.
[0022] Furthermore, in step S2-5, the reaction is heated to 90° C. to 110° C. and the reaction is carried out for 2-4 hours.
[0023] Beneficial effects: The present invention provides a composite electrode material and preparation method for a lithium-ion hybrid supercapacitor, and obtains a Co3O4@NiFe2O4 / rGO composite material; the Co3O4@NiFe2O4 / rGO composite material exhibits more excellent electrochemical properties, and a reversible redox reaction occurs, indicating that the Co3O4@NiFe2O4 / rGO composite material has good pseudocapacitive properties; the Co3O4@NiFe2O4 / rGO composite material is used as an electrode material, and when used, the discharge curve is significantly longer than that of the previous Co3O4-made electrode, and the Co3O4@NiFe2O4 / rGO composite material has a higher specific capacitance; the Co3O4@NiFe2O4 / rGO composite material simultaneously obtains high energy density, high power density and excellent cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Attached Figure 1 Scanning electron microscope images of NiFe2O4 and Co3O4@NiFe2O4 / rGO composites;
[0025] Attached Figure 2 is the scanning electron microscope image of Co3O4 nanorods;
[0026] Attached Figure 3 Schematic diagram of constant current charge and discharge test of Co3O4@NiFe2O4 / rGO composite material;
[0027] Attached Figure 4 These are the constant current charge and discharge test diagrams and comparison diagrams of Co3O4 and Co3O4@NiFe2O4 / rGO composites. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with the accompanying drawings.
[0029] As attached Figure 1 As shown, a composite electrode material for a lithium-ion hybrid supercapacitor includes nanorods composed of Co3O4; a plurality of NiFe2O4 nanosheet balls are attached to the surface of the nanorods composed of Co3O4.
[0030] As attached Figure 1 As shown, Figure 1 Figures a and b are scanning electron microscope images of NiFe2O4, and Figures c and d are scanning electron microscope images of Co3O4@NiFe2O4; in the obtained Co3O4@NiFe2O4 material, NiFe2O4 nanosheets grow on the surface of foam-type three-dimensional reduced graphene oxide rGO in the form of balls; and in Figure c, it can be seen that the NiFe2O4 nanosheets grow on the nanorods of Co3O4; the nanorods of Co3O4 and the NiFe2O4 nanosheet materials are attached to the surface of foam-type three-dimensional reduced graphene oxide rGO to form a Co3O4@NiFe2O4 / rGO composite material; the Co3O4@NiFe2O4 / rGO composite material is used as a composite electrode material for lithium-ion hybrid supercapacitors.
[0031] As attached Figure 2 As shown in FIG. 1 , the length of the nanorods made of Co3O4 ranges from 1.9 μm to 2.4 μm, and the width of the nanorods ranges from 0.15 μm to 0.28 μm. Figure 1 As shown, the diameter of the NiFe2O4 nanosheet spheres ranges from 2.3 μm to 2.8 μm.
[0032] A method for preparing a composite electrode material for a lithium-ion hybrid supercapacitor comprises the following steps:
[0033] S1-1, synthesizing graphene oxide GO solution by using improved Hummers method, soaking nickel foam in graphene oxide GO solution for a certain time, drying after soaking, and obtaining graphene oxide GO deposited on nickel foam; soaking time is 2-10h;
[0034] S1-2, placing the graphene oxide GO deposited on the nickel foam into a reactor lined with polytetrafluoroethylene, adding N2H4·H2O into the reactor, heating the reactor for reaction, taking out the reactor after the reaction is completed and cooling it to obtain a reduced graphene oxide rGO sample;
[0035] S1-3, soaking the reduced graphene oxide rGO sample in a mixed solution of FeCl3 and HCl for a certain period of time to etch and remove the foam nickel template; the soaking time is 3-5 hours, specifically 4 hours;
[0036] S1-4, cleaning the reduced graphene oxide rGO sample from which the foam nickel template is etched away, and heating and drying the cleaned reduced graphene oxide rGO sample to obtain foam-type three-dimensional reduced graphene oxide rGO.
[0037] A method for preparing a composite electrode material for a lithium-ion hybrid supercapacitor further comprises the following steps:
[0038] S2-1, dissolve Co(NO3)2·6H2O and urea in H2O and stir until clear to obtain a mixed solution A;
[0039] S2-2, adding the mixed solution A into a reactor containing the treated foam-type three-dimensional reduced graphene oxide rGO substrate, and heating the reactor for reaction;
[0040] S2-3, using water to wash the reaction kettle after the reaction in step S2-2, and heating to dry;
[0041] S2-4, dissolve Ni(NO3)2·6H2O, Fe(NO3)3·9H2O, NH4F and urea in H2O, and stir until clear to obtain a mixed solution B;
[0042] S2-5, adding the mixed solution B into the reaction kettle dried in step S2-3, and heating for reaction;
[0043] S2-6, using water to wash the reactor after the reaction in step S2-5, and heating to dry, and calcining the precursor at 345°C to 360°C for a certain time to obtain a Co3O4@NiFe2O4 / rGO composite material; the calcination time is 1.5h-2.5h, and the specific time is 2h.
[0044] In the step S1-2, the reaction kettle is heated to react at a temperature of 80° C. to 95° C. for 5-7 hours.
[0045] In the step S2-2, the reaction is carried out by heating the reactor to 110° C. to 130° C. for 4 to 8 hours.
[0046] In the step S2-5, the reaction is carried out by heating the reactor to 90° C. to 110° C. for 2-4 hours.
[0047] A three-dimensional carbon-based lithium-ion hybrid supercapacitor consists of a shell, a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte; the positive electrode sheet is composed of a three-dimensional reduced graphene oxide rGO substrate material, and the negative electrode sheet is mainly composed of a Co3O4@NiFe2O4 / rGO composite material supported on the three-dimensional reduced graphene oxide; the electrolyte is 1M LiPF6 dissolved in a mixed solution of ethylene carbonate / diethyl carbonate / dimethyl carbonate (EC / DEC / DMC) with a volume ratio of 1:1:1.
[0048] Example
[0049] The specific production steps of Co3O4@NiFe2O4 / rGO composite material are as follows:
[0050] S1-1, synthesizing graphene oxide GO solution by using improved Hummers method, soaking nickel foam with a thickness of 0.5-2 mm in the graphene oxide GO solution at room temperature of 20°C to 26°C for 2-10 hours, and drying for 12 hours after soaking to obtain graphene oxide GO deposited on the nickel foam;
[0051] S1-2, placing the graphene oxide GO deposited on the nickel foam into a reactor lined with polytetrafluoroethylene, adding 20 μL of N2H4·H2O into the reactor, heating the reactor to a high temperature environment of 90°C for 6 hours, and after the reaction is completed, taking out the reactor and cooling it to room temperature of 20°C to 26°C to obtain a reduced graphene oxide rGO sample;
[0052] S1-3, soaking the reduced graphene oxide rGO sample in a mixed solution of 0.5M FeCl3 and 1M HCl for 4 hours to etch and remove the nickel foam template;
[0053] S1-4. The reduced graphene oxide rGO sample from which the foam nickel template is etched away is washed in ethanol and deionized water. The washed reduced graphene oxide rGO sample is dried in an environment of 50°C to 70°C for 12 hours, specifically, dried in an environment of 60°C for 12 hours to obtain foam-type three-dimensional reduced graphene oxide rGO.
[0054] The following steps are also included:
[0055] S2-1, dissolve 0.7337 g of Co(NO3)2·6H2O and 1.89 g of urea in 100 ml of H2O, and stir until clear to obtain a mixed solution A;
[0056] S2-2, adding the mixed solution A into a reactor containing the treated foamed three-dimensional reduced graphene oxide rGO substrate, and heating to 120° C. for reaction for 4-8 hours;
[0057] S2-3, using water as the precursor, ultrasonically washing the reactor after the reaction in step S2-2 with ethanol, and drying at 50°C to 70°C, specifically at 60°C;
[0058] S2-4, dissolve 0.29 g of Ni(NO3)2·6H2O, 0.81 g of Fe(NO3)3·9H2O, 0.185 g of NH4F and 0.6 g of urea in 100 ml of H2O, and stir until clear to obtain a mixed solution B;
[0059] S2-5, adding the mixed solution B into the reaction kettle dried in step S2-3, and heating to 100° C. for reaction for 2-4 hours;
[0060] S2-6, using water and ethanol to ultrasonically wash the reactor after the reaction in step S2-5, and drying it at 50°C to 70°C, specifically at 60°C; and calcining the precursor at 350°C for 2h to obtain a Co3O4@NiFe2O4 / rGO composite material.
[0061] Co3O4 nanorods and NiFe2O4 nanosheets are attached to the surface of foamed three-dimensional reduced graphene oxide rGO to form a Co3O4@NiFe2O4 / rGO composite material; the Co3O4@NiFe2O4 / rGO composite material is used as a composite electrode material for a lithium-ion hybrid supercapacitor; for the obtained Co3O4@NiFe2O4 / rGO composite material, the actual measured length of the nanorods composed of Co3O4 is 2.2 μm and the width is 0.2 μm; the diameter range of the NiFe2O4 nanosheet is 2.4 μm.
[0062] The electrode composite material of the present invention was tested and compared with other electrode materials by electrochemical test; in the electrochemical test: the three-electrode system Co3O4@NiFe2O4 / rGO composite material, the auxiliary electrode was a platinum sheet electrode, the reference electrode was a saturated calomel electrode, and the electrolyte was 6M KOH.
[0063] As attached Figure 3 As shown, Figures a, b, and c are constant current charge and discharge tests at different current densities for 4-8h reaction time, and Figure d is 20 mA cm -1 Constant current charge-discharge test with different reaction times under the same conditions; From Figures a, b and c, it can be seen that the charge-discharge curves of Co3O4@NiFe2O4 / rGO composite material are quite symmetrical, that is, the reversible reduction-oxidation reaction indicates that it has good pseudocapacitance; Figure 3 The discharge curve of the electrode in Figure d for 8 hours is significantly longer than that of the previous two electrodes, indicating that it has a higher specific capacitance and better ability to charge and discharge quickly.
[0064] As attached Figure 4 As shown in Figures a and b, respectively, are the constant current charge and discharge tests of Co3O4 and Co3O4@NiFe2O4 / rGO composites at 8 hours, and Figure c is 20 mA cm -1 Figure 1 shows the constant current charge and discharge test comparison of Co3O4 and Co3O4@NiFe2O4 / rGO composite materials. Figure d shows the specific capacitance comparison of Co3O4 and Co3O4@NiFe2O4 / rGO composite materials at different current densities. From Figures a and b, it can be seen that the curves are quite symmetrical, which can indicate that a reversible redox reaction has occurred, that is, it has good pseudocapacitive properties; in Figure c, the discharge curve of the composite electrode is significantly longer than that of the previous Co3O4 electrode, indicating that it has a higher specific capacitance; Figure d shows the specific capacitance of the two electrodes at different current densities. The Co3O4@NiFe2O4 / rGO composite material has a higher specific capacitance at 1mA cm -1 The highest specific capacitance is 851.2F g -1 , which is 248.35F g of cobalt oxide Co3O4 -1 As the current density increases, the specific capacitance decreases. When the current density is 20 mA cm -1 At this time, the specific capacitance of Co3O4@NiFe2O4 / rGO composite material still retained as much as 81.56%, which is much higher than the specific capacitance of Co3O4.
[0065] The electrochemical tests show that as the reaction time of synthesizing Co3O4 on the three-dimensional reduced graphene oxide rGO substrate increases, the synthesized composite has a higher capacitance; compared with Co3O4, this Co3O4@NiFe2O4 / rGO composite material exhibits better electrochemical properties; at 1mA cm -2 The specific capacitance of the composite material is 851.2Fg -1 The Co3O4@NiFe2O4 / rGO composite material exhibits better electrochemical properties; the specific capacitance value of the composite material is 851.2F g-1 at a current density of 1 mA cm-2.
[0066] The above is only a description of the preferred embodiments of the present invention. Ordinary technicians in this technical field can make several modifications and optimizations based on the above disclosure without departing from the above basic principles. These improvements and optimizations should be regarded as the understood protection scope of the present invention.
Claims
1. A composite electrode material for a lithium-ion hybrid supercapacitor, characterized in that: It comprises a nanorod composed of Co3O4; a plurality of NiFe2O4 nanosheet balls are attached to the surface of the nanorod composed of Co3O4; NiFe2O4 nanosheets grow on Co3O4 nanorods; Co3O4 nanorods and NiFe2O4 nanosheets are attached to the surface of foamed three-dimensional reduced graphene oxide rGO to form a Co3O4@NiFe2O4 / rGO composite material; Co3O4@NiFe2O4 / rGO composite material is used as a composite electrode material for lithium-ion hybrid supercapacitors.
2. The composite electrode material for a lithium-ion hybrid supercapacitor according to claim 1, characterized in that: The length of the nanorods made of Co3O4 ranges from 1.9 μm to 2.4 μm, and the width of the nanorods ranges from 0.15 μm to 0.28 μm.
3. The composite electrode material for a lithium-ion hybrid supercapacitor according to claim 1, characterized in that: The diameter of the NiFe2O4 nanosheet ball ranges from 2.3 μm to 2.8 μm.
4. The method for preparing a composite electrode material for a lithium-ion hybrid supercapacitor according to claim 1, characterized in that: The following steps are involved: S1-1, synthesizing graphene oxide GO solution by using improved Hummers method, soaking nickel foam in the graphene oxide GO solution for a certain period of time, and drying after soaking to obtain graphene oxide GO deposited on the nickel foam; S1-2, placing the graphene oxide GO deposited on the nickel foam into a reactor lined with polytetrafluoroethylene, adding N2H4·H2O into the reactor, heating the reactor for reaction, taking out the reactor after the reaction is completed and cooling it to obtain a reduced graphene oxide rGO sample; S1-3, soaking the reduced graphene oxide rGO sample in a mixed solution of FeCl3 and HCl for a certain period of time to etch and remove the nickel foam template; S1-4, cleaning the reduced graphene oxide rGO sample from which the foam nickel template is etched away, and heating and drying the cleaned reduced graphene oxide rGO sample to obtain foam-type three-dimensional reduced graphene oxide rGO.
5. The method for preparing a composite electrode material for a lithium-ion hybrid supercapacitor according to claim 4, characterized in that: The following steps are also included: S2-1, dissolve Co(NO3)2∙6H2O and urea in H2O and stir until clear to obtain a mixed solution A; S2-2, adding the mixed solution A into a reactor containing the treated foam-type three-dimensional reduced graphene oxide rGO substrate, and heating the reactor for reaction; S2-3, washing the reaction kettle after the reaction in step S2-2 with ethanol, and heating to dry; S2-4, dissolve Ni(NO3)2∙6H2O, Fe(NO3)3∙9H2O, NH4F and urea in H2O, and stir until clear to obtain a mixed solution B; S2-5, adding the mixed solution B into the reaction kettle dried in step S2-3, and heating for reaction; S2-6. Wash the reaction kettle after the reaction in step S2-5 with ethanol, heat and dry it, and calcine the precursor at 345°C~360°C for a certain time to obtain a Co3O4@NiFe2O4 / rGO composite material.
6. The method for preparing a composite electrode material for a lithium-ion hybrid supercapacitor according to claim 4, characterized in that: In the step S1-2, the reactor is heated to react at a temperature of 80° C. to 95° C. for 5-7 hours.
7. The method for preparing a composite electrode material for a lithium-ion hybrid supercapacitor according to claim 5, characterized in that: In the step S2-2, the reaction is carried out by heating the reactor to 110° C. to 130° C. for 4 to 8 hours.
8. The method for preparing a composite electrode material for a lithium-ion hybrid supercapacitor according to claim 5, characterized in that: In the step S2-5, the reaction is carried out by heating the reactor to 90°C to 110°C for 2-4h.
Citation Information
Patent Citations
Full-pseudocapacitance symmetric supercapacitor and fabrication method thereof
CN110211811A
KR20200086189A
Cited By
High-energy-density supercapacitor electrode material and preparation method thereof
CN120954893A